Perancangan Sistem Penagihan (Invoice) Chemical Cleaningmenggunakan Metode Rapid Application Development (RAD)Untuk Jasa Konstruksi: Studi Kasus Pada Pt. Matura Jaya - Aulia, Anisa; Saputra, Meldi Anggara; Munawaroh, Siti (Teknik Informatika Fakultas Ilmu Komputer, 2025)
This study aims to design a web-based invoicing system for chemical cleaning services at PT. Matura Jaya using the Rapid Application Development (RAD) method. The previously used manual system caused various issues such as delivery delays, duplicate invoice numbers, and difficulties in payment tracking. The designed system includes features such as automated invoice generation, real-time payment status tracking, due date reminder notifications via email and WhatsApp, and integrated automatic tax calculations. The development process follows Rapid Application Development (RAD) stages, including planning, design, prototype development, testing, and implementation. The results indicate that the system significantly improves the efficiency of financial administration, reduces errors, and accelerates the billing process, thereby supporting better company financial management.